Modelling of badminton shuttlecock trajectories - Loo, Benjamin Zhen Yang (Nanyang Technological University, 2024)
This study investigates the trajectory of a badminton shuttlecock experiencing a crosswind. The main objective of this project is to design an experiment to provide insights into how a shuttlecock’s trajectory could be affected by wind by analysing the motion and forces of a shuttlecock experiencing different wind speeds. The Yonex Aerosensa 50 shuttlecock is the shuttlecock used for this Project. Four experiments were conducted using WindShaper, an open blower, to measure the deviation angles of a shuttlecock and the forces acting on it. The first two experiments showed that the deviation angles are almost directly proportional to the wind speeds. The last two experiments were unsuccessful in providing data to measure the forces acting on the shuttlecock, but computational fluid dynamics simulations (courtesy of NING Research, professional simulation engineering firm who partners on this project) were employed to indicate the magnitude of forces and attribute the failure in experiments. Insights from the study contribute to a better understanding of the motion of a shuttlecock experiencing crosswinds.